Independent Risk Factors for Positive and Negative Symptoms in Patients with Diabetic Polyneuropathy. (2nd July 2016) - Inoue, Reo; Sumitani, Masahiko; Yasuda, Tetsuyuki; Tsuji, Mayumi; Nakamura, Masaya; Shimomura, Iichiro; Shibata, Masahiko; Yamada, Yoshitsugu
ABSTRACT: Patients with diabetes occasionally develop diabetic polyneuropathy (DPN), which is characterized by both positive symptoms such as pain and negative symptoms such as numbness/dysesthesia. However, these symptoms have always been collectively analyzed to determine their risk factors. This study aimed to independently analyze the risk factors for neuropathic pain and numbness/dysesthesia in DPN patients. In total, 298 patients with diabetes (age: 61.1 ± 10.4 years; 176 male) were included. The relationships among the incidence of DPN and its clinical parameters were determined using logistic regression models. Then, the statistical model was applied in two groups of DPN patients: those with pain only or both pain and the negative symptoms (pain group; n = 25) and those with the negative symptoms only or both pain and the negative symptoms (numbness/dysesthesia group; n = 60). All logistic regression models were adjusted for the duration of diabetes, glycosylated hemoglobin levels, and age. The depression score was higher for patients with DPN than for those without, although it did not reach an abnormal level. An abnormal Achilles tendon reflex (ATR) and insulin treatment, but not smoking, hypertension, hyperlipidemia, and diabetic retinopathy, were associated with DPN. Furthermore, female sex and an abnormal ATR and insulin treatment were significant clinical features in the pain and numbness/numbness groups, respectively. Overweight and obesity were the common clinical features in both groups. We conclude that the positive and negative symptoms of DPN possibly have independent risk factors, suggesting different underlying mechanisms and the need for separate diagnosis and treatment.